Effect of Statins on Liver Function Tests (LFTs) in Patients with Diabetes Presenting in CMH Rawalakot - Zia, Tayyiba (Indus Journal of Bioscience Research, 2025)
Objectives: To find the effect of statin therapy on liver function tests in diabetic patients presenting at CMH Rawalakot. Study design: Qausi-experimental study. Place and duration of study: Department of Medicine, CMH, Rawalakot, from October 2024 to March 2025. Methodology: A total of 100 patients, aging between 40 to 70 years, diagnosed with type 2 diabetes since ≥1 year, and was not previously on statin therapy, were included in this study using consecutive sampling. All the demographics and related medical history was recorded. Baseline liver function tests (ALT, AST, ALP, GGT, and total bilirubin) and the blood glucose levels were recorded.  Patients were recommended Rosuvastatin 20 mg/day for 3 months. The primary objectives of the study was to find the impact of statin therapy on liver function tests in diabetic patients presenting at our hospital. Values of Pre- and post-treatment LFT were compared using the paired t-test, with a p-value